Work Role Transitions: A Study of American Expatriate Managers in Japan - Black, J. Stewart (Journal of International Business Studies, 1988)
Throughout the course of a career, an individual must make numerous role transitions, instigated through such events as overseas transfers, domestic transfers, promotions, company reorganizations, and inter-company job changes. This paper examines the relationships between several variables and work role transition in the case of an overseas assignment to Japan. Role ambiguity and role discretion were found to influence work adjustment, while predeparture knowledge, association with local nationals, and family's adjustment were found to correlate with general adjustment of American expatriate managers in Japan.